(untitled) (Conferencea, 2022)
The article presents a general understanding of language and communication between representatives of different cultures in the modern world. The role and place of language in the system of intercultural communication and ensuring intercultural harmony is analyzed. There are a number of rules aimed at the use of language to ensure successful intercultural communication. The article is also devoted to understanding the concept of "national character", which is one of the components of intercultural communication.